Respostas

2014-08-24T20:34:14-03:00
(3/2-1/3)²= 9/4-2*(3/2*1/3)+1/9 => 9/4-2*(3/6)+1/9 => 9/4-1+1/9

(-1/3+1/2)² = (1/2-1/3)² = 1/4-2*(1/2*1/3)+1/9 => 1/4-2*(1/6)+1/9 => 1/4-2/6+1/9

9/4-1+1/9  (mmc=36) => (81-36+4)/36= 49/36 ==>  49/36*36/1 = 1764/36=49
1/4-2/6+1/9 (mmc=36) => (9-12+4)/36 = 1/36   ==>
1 1 1
espero que de pra entender
No livro esta 49
as partes sublinhadas indicão a fração
2014-08-24T20:46:40-03:00
(3/2-1/3)²= 9/4-2*(3/2*1/3)+1/9 => 9/4-2*(3/6)+1/9 => 9/4-1+1/9

(-1/3+1/2)² = (1/2-1/3)² = 1/4-2*(1/2*1/3)+1/9 => 1/4-2*(1/6)+1/9 => 1/4-2/6+1/9

9/4-1+1/9  (mmc=36) => (81-36+4)/36= 49/36 ==>  49/36*36/1 = 1764/36=49
1/4-2/6+1/9 (mmc=36) => (9-12+4)/36 = 1/36   ==>